Sistem Informasi Yayasan Nusantara Terdidik Berbasis Website - Rahman, M. Aufi; Danny, Muhtajuddin; Nugroho, Agung (Teknik Informatika, Universitas Pelita Bangsa, 2023)
The activities carried out by the Nusantara Terdidik Foundation are still fairly conventional. The absence of a website that can contain information on every activity, activity results, latest news and fundraising, still makes it difficult for people to want to know more about the activities and activities of the Nusantara Terdidik Foundation which is engaged in education or cares about remote education. With the creation of this website-based information system, it is hoped that it can help the Educated Nusantara Foundation to be more easily accessible or seen by the wider community. Keywords: Information, Website, Foundation, Education